Pengaruh Program Sekolah Lapang Pengelolaan Tanaman Terpadu (SL-PTT) terhadap Pendapatan Petani Padi di Lahan Rawa Lebak Kecamatan Amuntai Utara Kabupaten Hulu Sungai Utara - Ruliyani Ruliyani; Emy Rahmawati; Nurmelati Septiana (AGRIDES: Jurnal Agribisnis Perdesaan, 2014)
Agriculture sector, especially rice, has important contribution on the economic development of Kabupaten Hulu Sungai Utara. Since 2012, the local government has optimized Field Schoof of Integrated Farming (SL-PTT) to increase the rice production and productivity by strengthening the informal education. The nature of education is creating partnership among farmers in solving problems, decision making, experience sharing, and field practice. Then, the increase of rice quantity and quality which lead to the rise of income is expected. The study is purposed: (1) to compare the total cost, revenue and income between SL-PTT farmer and non-SL-PTT; (2) to analyze the effect of SL-PTT program on the farmer income; and (3) to excavate the problem encountered by farmer. About 40 respondents were randomly selected from two villages (Muara Karangan and Kuangan). The results show that there is no significant different of cost, revenue, and profit between SL-PTT and nonSL-PTT farmer. Based on the t-test , the program does not significantly affect the farmer income. The problem encountered in rice farming varied from flood , pest attack, doing adequate fertilizing , limited accessibility, and limited fund.